Combinatorial Control of Gene Expression - Soumya Bhattacharjee (BioMed Research International, 2013)
The complexity and diversity of eukaryotic organisms are a feat of nature’s engineering. Pulling the strings of such an intricate machinery requires an even more masterful and crafty approach. Only the number and type of responses that they generate exceed the staggering proportions of environmental signals perceived and processed by eukaryotes. Hence, at first glance, the cell’s sparse stockpile of controlling factors does not seem remotely adequate to carry out this response. The question as to how eukaryotes sense and respond to environmental cues has no single answer. It is an amalgamation, an interplay between several processes, pathways, and factors—a combinatorial control. A short description of some of the most important elements that operate this entire conglomerate is given in this paper.